If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -5(2x + 9) = 4 Reorder the terms: 7 + -5(9 + 2x) = 4 7 + (9 * -5 + 2x * -5) = 4 7 + (-45 + -10x) = 4 Combine like terms: 7 + -45 = -38 -38 + -10x = 4 Solving -38 + -10x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '38' to each side of the equation. -38 + 38 + -10x = 4 + 38 Combine like terms: -38 + 38 = 0 0 + -10x = 4 + 38 -10x = 4 + 38 Combine like terms: 4 + 38 = 42 -10x = 42 Divide each side by '-10'. x = -4.2 Simplifying x = -4.2
| 2x-7+x+1=180 | | 10=y*20 | | 4b^2-6+10b=0 | | 7+(2x*4)=(x*-18)+2 | | 2t^2+5t+2=2 | | 4x-8=2x-3+3x-5 | | 8([15-y]/7)=-11-5y | | x(2x-4)= | | (x+5)(4x-1)+2(2-8x)(x-5)=0 | | 3x+7x+21=-29 | | (x-5)(4x-1)+2(2-8x)(x-5)=0 | | 4x-8+x=2x-3 | | x(2y-1)= | | 5x+7=3x+5+2x | | 14.7-40*.11= | | 9x-24+24=0 | | 9x-1/2=9 | | 5x+7=3x+5+x | | 3(C+8)=12 | | 5x2y2/xy | | 9x^4-13x+4=0 | | x-9/7=1 | | -16=4+4x | | 8(2-3x)+11=7(3x-2)+10 | | (5+8x)-2x-4= | | 2(-x+8)=-18 | | y-x-2=0 | | 7(3s+9)=279 | | f(4)=2(4)-3 | | y^2=22.5(22.5-y) | | 4(-x+6)=21 | | 6(2l+5)=42 |